Estimated Life Loss of a 3-Phase Induction Motor Based on Insulation Resistance Test at PT. Delta Jaya Mas - Widagdo, Reza Sarwo; Slamet, Puji; Andriawan, Aris Heri (Electrical Engineering, Universitas Mercu Buana, 2024)
At the company PT. Delta Jaya Mas induction motors are very necessary to run machines in the production process. An induction motor consists of a rotor and stator with insulation resistance. Insulation Resistance (IR) is a measure of the ability of the insulation in the winding to withstand current. Insulation resistance testing is needed to determine the condition of the insulation which is influenced by humidity, environmental temperature and operating time. This test procedure is regulated in the IEEE Std 43-2000 standard. The use of an appropriate insulation tester and routine testing is important to maintain the insulation resistance value and prevent accidents and damage to 3-phase induction motors. Testing is carried out when the motor is turned off to avoid component damage. Polarization index data is taken by testing the insulation resistance for 1 to 10 minutes. The test was carried out on the insulation resistance of a three-phase induction motor with a power of 75 kW which showed a value of 515 MΩ to 602 MΩ when it was in a damaged condition with one phase having a value of 0 MΩ indicating a short or short circuit condition. After repair the motor has an insulation resistance of 2000 MΩ. After operating for 3 months the decrease in resistance that occurred per month was 11.6 MΩ and the polarization index test was 3.5 MΩ. An insulation resistance of 2000 MΩ can be expected to last for 14 years if degradation occurs consistently.